Bobby Seale [appearance at Cal Poly] - Bobby Seale::::::::: (1972)
Recording of speech made by Bobby Seale (co-founder of the Black Panther Party and activist for the Civil Rights Movement) on Cal Poly campus. Side B is a Q and A session after Seale's speech.